Correlational of adaptive reasoning and problem-solving level using AKMI task model in scientific context - kumalasari, dwiayu; Sulistyawati, Eka; Wulan, Eka Resti (LINEAR: Journal of Mathematics Education, 2025)
This study is based on the literature finding that problem-solving ability and adaptive reasoning ability are interconnected but have not been widely studied empirically, using AKMI model questions at the MTs level. This research aims to describe and determine the relationship between these two abilities in solving AKMI model questions at the HOTS level with a scientific context for MTs students in Kediri City. This research uses a quantitative survey approach with a population of 160 students and a sample of 129 respondents from schools participating in the 2024 AKMI program. The research instrument consists of two AKMI-model questions at the HOTS level with a scientific context, which were developed based on indicators of problem-solving ability and adaptive reasoning using PLSV material. The instrument has undergone expert validation, with Aiken's V indices of 0.8913 and 0.875, and shows high reliability based on a Cronbach's Alpha test result of 0.821. The data obtained were analyzed descriptively and inferentially using the Spearman Correlation Test. The results of the descriptive analysis showed that students' problem-solving abilities were divided into three categories: 22 students were in the low category, 79 students were in the medium category, and 28 students were in the high category. Meanwhile, the results of the Spearman correlation test showed a positive relationship between adaptive reasoning ability and problem-solving ability. This finding indicates the importance of learning strategies that can accommodate both abilities.